Chemical Synthesis of the Fluorescent, Cyclic Dinucleotides cthGAMP. (10th March 2022) - Veth, Simon; Fuchs, Adrian; Özdemir, Dilara; Dialer, Clemens; Drexler, David Jan; Knechtel, Fabian; Witte, Gregor; Hopfner, Karl‐Peter; Carell, Thomas; Ploetz, Evelyn
Abstract: The cGAS‐STING pathway is known for its role in sensing cytosolic DNA introduced by a viral infection, bacterial invasion or tumorigenesis. Free DNA is recognized by the cyclic GMP‐AMP synthase (cGAS) catalyzing the production of 2', 3'‐cyclic guanosine monophosphate‐adenosine monophosphate (2', 3'‐cGAMP) in mammals. This cyclic dinucleotide acts as a second messenger, activating the stimulator of interferon genes (STING) that finally triggers the transcription of interferon genes and inflammatory cytokines. Due to the therapeutic potential of this pathway, both the production and the detection of cGAMP via fluorescent moieties for assay development is of great importance. Here, we introduce the paralleled synthetic access to the intrinsically fluorescent, cyclic dinucleotides 2'3'‐c th GAMP and 3'3'‐c th GAMP based on phosphoramidite and phosphate chemistry, adaptable for large scale synthesis. We examine their binding properties to murine and human STING and confirm biological activity including interferon induction by 2'3'‐c th GAMP in THP‐1 monocytes. Two‐photon imaging revealed successful cellular uptake of 2'3'‐c th GAMP in THP‐1 cells. Abstract : The cyclic dinucleotide (CDN) 2'3'‐cGAMP is an essential second messenger for the innate immune system of mammals. The organic synthesis of an intrinsically fluorescent mimic provided large quantities for cell feeding studies, examination of biological activity and two‐photon excitation microscopy.